Bacteriocins with a broader antimicrobial spectrum prevail in enterococcal symbionts isolated from the hoopoe's uropygial gland. Issue 3 (16th May 2013) - Ruiz‐Rodríguez, Magdalena; Martínez‐Bueno, Manuel; Martín‐Vivaldi, Manuel; Valdivia, Eva; Soler, Juan J.
Abstract: The use of compounds produced by symbiotic bacteria against pathogens in animals is one of the most exciting discoveries in ecological immunology. The study of those antibiotic metabolites will enable an understanding of the defensive strategies against pathogenic infections. Here, we explore the role of bacteriocins explaining the antimicrobial properties of symbiotic bacteria isolated from the uropygial gland of the hoopoe ( Upupa epops ). The antagonistic activity of 187 strains was assayed against eight indicator bacteria, and the presence of six bacteriocin genes was detected in the genomic DNA. The presence of bacteriocin genes correlated with the antimicrobial activity of isolates. The most frequently detected bacteriocin genes were those encoding for the MR10 and AS‐48 enterocins, which confer the highest inhibition capacity. All the isolates belonged to the genus Enterococcus, with E. faecalis as the most abundant species, with the broadest antimicrobial spectrum and the highest antagonistic activity. The vast majority of E. faecalis strains carried the genes of MR10 and AS‐48 in their genome. Therefore, we suggest that fitness‐related benefits for hoopoes associated with harbouring the most bactericidal symbionts cause the highest frequency of strains carrying MR10 and AS‐48 genes. The study of mechanisms associated with the acquisition and selection of bacterial symbionts by hoopoes is necessary, however, to reach further conclusions.